Does coronary calcium scoring adds value to cardiovascular risk prediction in asymptomatic population?. (25th November 2020) - Serrao, M; Temtem, M; Pereira, A; Monteiro, J; Santos, M; Sousa, A.C; Henriques, E; Freitas, S; Ornelas, I; Drumond, A; Palma Dos Reis, R; Mendonca, M.I
Abstract: Background: Despite being a controversial subject, multiple guidelines mention the use of Coronary Artery Calcification (CAC) scoring in the cardiovascular risk prediction, in asymptomatic population. The inclusion of CAC scoring in traditional risk models may help in decision-make providing better cardiovascular risk stratification. Purpose: The aim of our study is to estimate the impact of CAC scoring in cardiovascular events risk prediction in a model based on traditional risk factors (TRFs). Methods and results: The study consisted of 1052 asymptomatic individuals free of known coronary heart disease, enrolled from GENEMACOR study and referred for computed tomography for the CAC scoring assessment. A cohort of 952 was followed for a mean of 5.2±3.2 years for the primary endpoint of all-cause of cardiovascular events. The following traditional risk factors were considered: (1) current cigarette smoking, (2) dyslipidemia, (3) diabetes mellitus, (4) hypertension and (5) family history of coronary heart disease. Among this population, the extent of CAC differs significantly between men and women in the same age group. Therefore, the distribution of CAC score by age and gender was done by using the Hoff's nomogram (a). According to this nomogram, 3 categories were created: low CAC (0≤CAC<100 and P<50); moderate CAC (100≤CAC<400 or P50–75) and high CAC (CAC≥400 or P>75). Two Cox regression models were created, the first only with TRFs and the second adding the CAC severity categories. When including CAC categories to the TRFs, the higher severity level presented a significant risk of MACE occurrence with an HR of 4.39 (95% CI 1.83–10.52; p=0.001). Conclusion: Our results point to the importance of the inclusion of CAC in both primary and secondary prevention to an improved risk stratification. Larger prospective multicentre cohorts with longer follow-up should reproduce and validate these findings. Funding Acknowledgement: Type of funding source: None